Challenges of Medical Residency in Geriatrics in Brazil During the Covid-19 Pandemic - Marco Túlio Gualberto Cintra; Daniel Lima Azevedo; Flávia Campora; Clarice Câmara Correia; Renato Gorga Bandeira de Mello (Brazilian Society of Geriatrics and Gerontology, 2024)
None.